2016
DOI: 10.1177/1533034615605248
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Clinical Utility of Glypican 3 as a Serum Marker for the Diagnosis of Hepatocellular Carcinoma

Abstract: Glypican-3 has been reported to be one of the most promising serum markers for hepatocellular carcinoma. This study aimed to assess the clinical utility of serum glypican 3 for the diagnosis of hepatocellular carcinoma. We recruited consecutive patients on a large scale, 283 with hepatocellular carcinoma, 445 with chronic hepatic diseases, and 162 normal controls, to assess the diagnostic accuracy of serum glypican 3 for hepatocellular carcinoma by enzyme-linked immunosorbent assay. In addition, we further ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Several studies have confirmed the expression of GPC3 in regenerative nodules, hepatitis C samples, cirrhosis and even in normal liver tissues1935. In a recent study, Yasuda et al 27.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies have confirmed the expression of GPC3 in regenerative nodules, hepatitis C samples, cirrhosis and even in normal liver tissues1935. In a recent study, Yasuda et al 27.…”
Section: Discussionmentioning
confidence: 92%
“…Some found that GPC3 is a more sensitive and specific serum marker than AFP for HCC1617182526. Conversely, others showed that GPC3 is not a good serum marker for HCC1927282930. As a result, the diagnostic value of serum GPC3 in patients with HCC remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was indicated by both real-time reverse transcriptase-polymerase chain reaction and immunohistochemistry [23]. However, when GPC3 is compared to AFP, the serum GPC3 diagnostic value in HCC remains controversial [14]. The virus infection, HCV or HBV, and GPC3 antibody source were not the culprits for this conflict.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the hepatocytes of healthy individuals and hepatitis patients, many studies reported an increased GPC3 expression in HCC tissues [9]. However, many studies suggested that serum GPC3 is a specific HCC biomarker owing to its higher levels in HCC than that in healthy or hepatitis individuals [10,11]; conflicting results were obtained by other studies [12][13][14]. There is an agreement between most of these studies and others that GPC3 alone is not a promising HCC serum maker.…”
Section: Introductionmentioning
confidence: 99%